The Effect of Changing The Net Assets of the Economic Unit on The Fair Value - Hamad Hadi, Hadi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The cognitive and conceptual framework of the study was formulatedthrough the independent variable, which is the ownership structure and itsimpact on the intermediate variable, which is the profit distribution policy,and the dependent variable, which is the real value of shares .Therefore,the study was built on its problem through a set of questions raised by theresearcher, namely, whether there are clear effects of a change in theownership structure on the intermediate variable on the real value ofshares .The premise of the study was that measuring and presenting thenet assets of the economic unit on the basis of fair value makes thedecisions of current and prospective investors more rational, especially asthis reflects the current status of the value of the economic unit. The studyconcluded that investors should follow the changes in the ownershipstructure of Iraqi enterprises because they affect the real value of sharesin order to access information that enables them to make investmentdecisions.